KLASIFIKASI ULANG KAWASAN HUTAN LINDUNG DAN ARAHAN FUNGSI KAWASAN HUTAN LINDUNG DI KECAMATAN BAJUIN KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Aipansyah, Aipansyah; Suyanto, Suyanto; Hafizianor, Hafizianor (Jurnal Hutan Tropis, 2024)
The conservation of protected forest areas is crucial for maintaining biodiversity and ecosystem functionality. To safeguard the sustainability of these forests, it is imperative to reevaluate and redefine their boundaries to enhance management and protection. This study's main objective is to analyze the outcomes of evaluating the protected forest area boundaries in Bajuin District. The analysis utilizes digital data and spatial data techniques, employing the overlay method to generate a new map. The new map is then subjected to the scoring method, yielding a comprehensive map displaying forest area functionalities. The comparison between the protected forest maps from the South Kalimantan RTRWP 2015-2035 and the scoring results revealed a significant difference of 5,485.48 ha in the protected forest area. According to the South Kalimantan RTRWP 2015-2035, the protected forest area covers 4,000.20 ha, whereas the scoring results' map extends the protected area to 9,485.48 ha based on the latest database. It is essential to retain the protected forest area of 1,578.47 ha, which includes regions with a slope of >45%, as it meets the criteria for conservation. To ensure the sustainable preservation of these critical ecosystems, local authorities must take into account the findings of this evaluation. By redefining and accurately delineating the protected forest boundaries, appropriate measures can be implemented to mitigate threats from population growth, encroachment, and resource exploitation. Adequate protection and management strategies will safeguard biodiversity and promote the continued ecological functioning of these vital natural resources in Bajuin District, South Kalimantan Province.